Análisis jurídico y doctrinario de la imprescriptibilidad en el delito de femicidio y su juzgamiento en ausencia - Songor Chalco, Génesis Lucía (2024)
The present work of curricular integration entitled: "Legal and doctrinal analysis of the imprescriptibility of the crime of femicide and its trial in absentia", focuses on evaluating the impact of these legal mechanisms applied in the reality of our country, as a guarantee for the administration of justice, protection and comprehensive reparation for the victims of femicide. Through a review of the literature and the exploration of cases, the legal and doctrinal foundations that support the application of these measures are examined, as well as their introduction in other legal systems. It considers the statute of limitations on the criminal action, the suspension of the order to call for trial, and analyses how the non-applicability of statutes of limitations and trial in absentia in cases of femicide could strengthen the Ecuadorian legal system. It also discusses the need to reform Ecuadorian legislation to incorporate these measures in order to prevent impunity and provide justice for victims of femicide and their families. Also, within the present work of curricular integration, materials and methods were applied that allowed the development of the research, such as interviews and surveys of legal professionals, whose results served to know the different problems that arise because of this social reality, allowing to establish guidelines that help to find the most viable way for the procedure and also to find the solution to apply the imprescriptibility and its trial in absentia in the crime of femicide.